Effect of Mouthwashes on Solubility and Sorption of Restorative Composites - José Pereira Leal; Jaqueline Damasceno da Silva; Rafaelle Fernanda Melão Leal; Carlos da Cunha Oliveira-Júnior; Vera Lúcia Gomes Prado; Glauber Campos Vale (International Journal of Dentistry)
Objective. Composites sorption and solubility can be precursors of several chemical and physical processes, which lead to deleterious effects on the polymer structure. This study evaluated the effect of mouthwashes on solubility and sorption of composite resins. Materials and Methods. Forty-two specimens of each evaluated composite (Filtek Bulk Fill Flow, Opallis Flow, Durafill VS, and Filtek Z350) were prepared and randomized into seven groups for each solution (mouth rinses with and without alcohol and distilled water) and stored for seven days. Solubility and sorption tests were performed according to ISO4049. Data were analyzed using 2-way-ANOVA followed by Tukey’s test for means comparison (α=0.05). In addition, paired t-test was performed to analyze the alcohol effect on the studied composite resin properties. Results. Listerine Cool Mint (containing alcohol in its composition) caused the greatest degree of sorption for all composites tested in comparison to other rinses, while for solubility this behavior was observed for Opallis Flow and Durafill VS composite resins (p<0.05). Regarding the composites, Opallis Flow showed the highest sorption and solubility values in general (p<0.05). Conclusion. Overall, the sorption and solubility of composites were higher in mouthwashes containing alcohol in its composition, with Opallis Flow being the most affected composite resin.